(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2018)
Its fundamental to understand the financial system as intermediation medium in the money market. If a person keeps money at home, doesnt save money as she believes, but removes money of the economy. The saving volume problem in Argentina is explained as much by financial exclusión as by lack of trust of people able to get into the banking system. New products and fintech services that have electronic money as basis, allow in this context to achieve through transformative and additive models, quantitative and qualitative variations, respectively. Although the fintech ecosystem is large, the focus on payment methods is based on the existence of successful cases in many countries, even in Latin America, thus having in Argentina the potential to reduce the population cash demand and keep the money into the financial system.